Unintentional training? Consequences of naturalistic parent-guided positioning - An, Ran; Libertus, Klaus (Frontiers in Developmental Psychology, 2025)
IntroductionEarly motor skills are an essential part of healthy development. Previous research has demonstrated that intentional interventions may facilitate the emergence of key motor milestones such as grasping, sitting, crawling, or walking. However, less is known about the impact of less formal and intense practice opportunities on infant motor development. The current study fills this gap by examining the effects of brief, parent-guided postural positioning for the assessment of their infant's motor behavior. Critically, the parent-guided positioning lasted mere minutes and was not designed as an intervention.MethodsA sample of 81 parent-infant dyads participated in a longitudinal remote observation study conducted entirely via video conference. Dyads were divided into a “observed” and an “unobserved” group. The “observed” group experienced a total of 8 parent-guided positioning observations lasting a combined 16 min over an 8-week period just about 2 min of positioning experiences per week. The “unobserved” group was not observed and did not experience parent-guided positioning.ResultsComparing infant development between the groups at 6 and 10 months of age, results reveal higher scores in both motor and language domains for infants in “observed” group.DiscussionThese results demonstrate even brief engagement in new motor skills, or the indirect influence these engagements have on parenting behavior, may have cascading effects on concurrent and subsequent development.